Psychological and neuropsychological clinical impact in brain cancer patients and evidence-based psychological intervention: a systematic review of the literature - Pasquale Caponnetto; Giulia Schilirò; Marilena Maglia; Graziella Chiara Prezzavento; Chris Baeken; Maria Catena Quattropani (Health Psychology Research)
# Background